Monitoring ecological change during rapid socio-economic and political transitions: Colombian ecosystems in the post-conflict era. Issue 76 (October 2017) - Sierra, Carlos A.; Mahecha, Miguel; Poveda, Germán; Álvarez-Dávila, Esteban; Gutierrez-Velez, Víctor H.; Reu, Björn; Feilhauer, Hannes; Anáya, Jesús; Armenteras, Dolors; Benavides, Ana M.; Buendia, Corina; Duque, Álvaro; et al.
Highlights: Colombia is undergoing large socio-economic and political changes with unknown consequences for ecosystems and the services they provide. We review the capacity of Colombia to monitor ecosystems and how they change over time. We found that many programs are already in place that go in this direction. However, there is a large gap in terms of synthesis of existing information. Also, a system that consistently monitors ecosystem variables is urgently needed. To increase Colombia's ability to respond to these transformations, we propose a set of actions to facilitate dialog, synthesis, and monitoring capacity. Abstract: After more than 50-years of armed conflict, Colombia is now transitioning to a more stable social and political climate due to a series of peace agreements between the government and different armed groups. Consequences of these socio-economic and political changes on ecosystems are largely uncertain, but there is growing concern about derived increases in environmental degradation. Here, we review the capacity of Colombia to monitor the state of its ecosystems and their rate of change over time. We found several important programs currently set in place by different institutions as well as by independent groups of scientists that address different aspects of environmental monitoring. However, most of the current initiatives could be improved in terms of data coverage, quality and access, and could be better articulated among each other. We propose a set of activities that would increase the capacity of Colombia to monitor its ecosystems, provide useful information to policy makers, and facilitate scientific research. These include: 1) the establishment of a national center for ecological synthesis that focuses on analyzing existing information; 2) the establishment of an ecological observatory system that collects new information, integrates remote sensing products, and produces near real-time products on key ecological variables; and 3) the creation of new platforms for dialog and action within existing scientific and policy groups.